Sensitivity of bronchial receptors under the effect of tobacco smoke in the conditions of various activity of the thyroid gland in children. - Bashkirova, N. S.; Vуsochina I. L. (Medicni Perspektivi, 2019)
The role of the initial hormonal profile disorders of the system “pituitary – thyroid” in the emergence of a bronchospasm in response to exogenic stimuli has not been finally determined. The aim of our research was to investigate the character and degree of the relationship between bronchial hypersensitivity in children exposed to smoking and the functional activity of the thyroid gland. The research involved 74 patients aged 10 to 17 years. Sixteen children were not exposed to tobacco smoke, 50 children were passive smokers, and 8 of the children surveyed smoked actively. To investigate the level of bronchial sensitivity, a bronchial provocation test with a non-specific stimulus – bronchoconstrictor acetylcholine was carried out. We assayed the functional state of the thyroid gland by the level of free triiodothyronine (FT3), free thyroxin 4 (FT4) and thyroid stimulating hormone (TSH), identified by Enzyme-linked Immunosorbent Assay (ELISA) (Alkor Bio, Russia). Indicators of hormones of a thyroid gland in most of the examined children did not differ from standard values for healthy children. Analysis of the results of the inhaled bronchial provocation test with acetylcholin showed that the state of non-specific bronchial hypersensitivity was observed in 2 active smokers and in none of the passive smokers and non-smokers (χ2=15,4>χ201=9,21 або р<0,01). According to our data, in children with hypothyroidism, under the effect of tobacco smoke, changes in the functional state of sensitive bronchial receptors do not occur. Among 2 children who had an increased activity of the thyroid gland (hyperthyroidism), one child from the group of smokers had an increased bronchial sensitivity by the results of the acetylcholine test (p>0.05). According to our data, changes in the functional status of sensitive bronchial receptors (cholinergic receptors) resulting from exposure to tobacco smoke in children exposed to tobacco smoke, active or passive, do not depend on the functional state of the thyroid gland (Рχ2>0,05).